Sosialisasi dan Pelatihan Manajemen Kearsipan Dokumen Kebencanaan, serta Penguatan Tata Kelola Keuangan pada MDMC Kota Palangka Raya - Ainun Jariah; Devi Yuliantina; Bayu Suratmoko; Jaemi Wahyudi; Anggelina Hariyanti; Triwik Puji Rahayu (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to increase the capacity of disaster archival document management and strengthen financial governance within the Muhammadiyah Disaster Management Center (MDMC) in Palangka Raya City. Orderly, systematic, and accountable archive management is a crucial factor in supporting a rapid, precise, and coordinated disaster response. Furthermore, transparent and efficient financial governance is the foundation for program sustainability and public trust in the organization. This training program is designed to provide MDMC administrators and volunteers with a comprehensive understanding of the principles, procedures, and best practices in disaster archive management and organizational finances. The implementation method includes presentations through interactive lectures combined with group discussions to identify real-world problems and solutions. Participants also have the opportunity to engage in hands-on practice, such as compiling disaster archival documents, managing archive databases, and creating simple financial reports in accordance with nonprofit accounting standards. Furthermore, this training introduces national regulations related to archiving and data protection, ensuring that practices are aligned with statutory provisions. The results of the training demonstrated an increased understanding of the participants regarding the importance of archive management and financial governance, as evidenced by their ability to systematically organize documents and present accountable financial reports. It is hoped that, after the training, participants will be able to consistently apply these principles in MDMC's operational activities. This will create a well-organized documentation system, accountable financial management, and an MDMC institution that is increasingly professional, effective, and responsive to community needs in emergency situations. This activity is a strategic step to strengthen MDMC's role as the vanguard in disaster management at the local and national levels.